Diuretic Resistance Management in a Patient with Type I Cardiorenal Syndrome: A Case Report - Mochamad Yusuf; Hendri Susilo (Indian Journal of Forensic Medicine & Toxicology, 2021)
Diuretic resistance is commonly found as a problem in acute heart failure (AHF). A further understanding of diuretic response could lead to improved personal approaches for treating patients with AHF. A 48 yo male suffered shortness of breath with a history of hypertension and DM. The patient was diagnosed as Ischemic Cardiomyopathy with Type I Cardiorenal Syndrome. The patient was given a 40 mg continued by 80 mg intravenous furosemide and low dose dobutamine pump. As the patient had zero urine production, a 160 mg intravenous furosemide followed by 15 mg/hr. After high-dose furosemide was given, the urine production was increased and the patient showed improved signs and symptoms. Deteriorating kidney function and bad response to diuretics is a principal clinical problem in AHF. Some treatment strategies include a combination of diuretic therapy, an increased dose of intravenous loop diuretics, and ultrafiltration. However, this patient gave good respond only to high doses of loop diuretics.